Microfacies and diagenesis of older Pleistocene (pre‐last glacial maximum) reef deposits, Great Barrier Reef, Australia (IODP Expedition 325): A quantitative approach. Issue 6 (8th May 2013) - Gischler, Eberhard; Thomas, Alex L.; Droxler, André W.; Webster, Jody M.; Yokoyama, Yusuke; Schöne, Bernd R.; Porta, Giovanna Della
Abstract During Integrated Ocean Drilling Program Expedition 325, 34 holes were drilled along five transects in front of the Great Barrier Reef of Australia, penetrating some 700 m of late Pleistocene reef deposits (post‐glacial; largely 20 to 10 kyr bp) in water depths of 42 to 127 m. In seven holes, drilled in water depths of 42 to 92 m on three transects, older Pleistocene (older than last glacial maximum, >20 kyr bp) reef deposits were recovered from lower core sections. In this study, facies, diagenetic features, mineralogy and stable isotope geochemistry of 100 samples from six of the latter holes were investigated and quantified. Lithologies are dominated by grain‐supported textures, and were to a large part deposited in high‐energy, reef or reef slope environments. Quantitative analyses allow 11 microfacies to be defined, including mixed skeletal packstone and grainstone, mudstone‐wackestone, coral packstone, coral grainstone, coralline algal grainstone, coral‐algal packstone, coralline algal packstone, Halimeda grainstone, microbialite and caliche. Microbialites, that are common in cavities of younger, post‐glacial deposits, are rare in pre‐last glacial maximum core sections, possibly due to a lack of open framework suitable for colonization by microbes. In pre‐last glacial maximum deposits of holes M0032A and M0033A (>20 kyr bp), marine diagenetic features are dominant; samples consist largely of aragonite and high‐magnesium calcite. Holes M0042A and M0057A, which contain the oldest rocks (>169 kyr bp), are characterized by meteoric diagenesis and samples mostly consist of low‐magnesium calcite. Holes M0042A, M0055A and M0056A (>30 kyr bp), and a horizon in the upper part of hole M0057A, contain both marine and meteoric diagenetic features. However, only one change from marine to meteoric pore water is recorded in contrast with the changes in diagenetic environment that might be inferred from the sea‐level history. Values of stable isotopes of oxygen and carbon are consistent with these findings. Samples from holes M0032A and M0033A reflect largely positive values (δ18O: −1 to +1‰ and δ13C: +1 to +4‰), whereas those from holes M0042A and M0057A are negative (δ18O: −4 to +2‰ and δ13C: −8 to +2‰). Holes M0055A and M0056A provide intermediate values, with slightly positive δ13C, and negative δ18O values. The type and intensity of meteroric diagenesis appears to have been controlled both by age and depth, i.e. the time available for diagenetic alteration, and reflects the relation between reef deposition and sea‐level change.